Penerapan Disiplin Kerja pada UPTD Puskesmas Cikampek di Kabupaten Karawang - Rio Firmansyah; Uus MD Fadli; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to analyze the application of human resource discipline, especially among Cikampek Community Health Center UPTD employees in carrying out and carrying out their obligations, as well as complying with all applicable regulations. This research uses a quantitative approach with data collection techniques using questionnaires and observation as well as document review, while the data analysis technique used is descriptive statistics with the help of the SPSS (Statistical Program for Social Science) program to test the validity and reliability of the data. In this research, there were 58 respondents who were obtained using the Slovin formula and determining respondents using probability sampling techniques to answer the questionnaire given. The results of the research show that the level of employee discipline at the Cikampek Community Health Center UPTD can be said to be quite good. This can be seen from the employees who tend to be disciplined, although there are still some employees who have a low level of discipline. Judging from five aspects, namely attendance, evaluation, standards, vigilance and ethics, obtaining the largest average number in the very good category with a percentage of 75.1%, thus the role of the Head of the Cikampek Community Health Center UPTD and the awareness of each Cikampek Community Health Center UPTD employee is very important in improving discipline.